Telomere length is correlated with mitochondrial DNA copy number in intestinal, but not diffuse, gastric cancer - Jung, Soo-Jung (Oncol Lett, 2017)
A positive correlation between telomere length and mitochondrial DNA (mtDNA) copy number has previously been observed in healthy individuals, and in patients with psychiatric disorders. In the present study, telomere length and mtDNA copy number were evaluated in gastric cancer (GC) tissue samples. DNA was extracted from 109 GC samples (including 82 intestinal, and 27 diffuse cases), and the telomere length and mtDNA copy number were analyzed using a quantitative-polymerase chain reaction assay. The relative telomere length and mtDNA copy number in tumor tissue, as compared with in normal tissue, (mean ± standard deviation) in all GC samples were 11.48±1.14 and 14.86±1.35, respectively. Telomere length and mtDNA copy number were not identified as exhibiting clinical or prognostic value for GC. However, positive correlations between telomere length and mitochondrial DNA copy number were identified in GC (r=0.408, P<0.001) and in the adjacent normal mucosa (r=0.363; P<0.001). When stratified by Lauren classification, the correlation was identified in intestinal type GC samples (r=0.461; P<0.001), but not in diffuse type GC samples (r=0.225; P=0.260). This result indicated that loss of the correlation of telomeres and mitochondrial function may induce the initiation or progression of GC pathogenesis.